Inocybe kusadasiensis (Inocybaceae: Agaricomycetes), a new species from Turkey - Kaygusuz, Oğuzhan; Bandini, Ditte; Çeli̇k Ali̇ (Phytotaxa, 2022)
Inocybe kusadasiensis sp. nov., a novel species which was collected from Pinus brutia forest near Kuşadası (Turkey), in the coastal area of Aegean Sea, is introduced with full descriptions of macro and microscopic features, field photograph and line-drawings. A phylogenetic analysis of sequence data for the nuc rDNA internal transcribed spacer region ITS1-5.8S-ITS2 (ITS) indicated and supported the taxonomic uniqueness of the present new species which belongs to the genus Inocybe.